Development of Android-Based Learning Media: a Literature Review - Darwin, David; Rafli, Zainal; Setiadi, Samsi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The development of information and communication technology such as android has not been widely used to support the learning process. Supposedly technological advances such as android can be utilized in the learning process. This study aims to discover some of the inventions of Android-based learning media that are currently being developed to support an efficient and effective learning process. The research design was in the form of a review of journals published in the Sinta database with the keywords "development of learning media" and "android-based learning media". The data used is in the form of journals related to the development of Android-based learning media in the 2016-2022 period. Based on the analysis that has been done, Android-based learning media that has been developed are in the form of video, PowerPoint, and applications. This Android-based learning media has proven successful in increasing student understanding, student motivation, and student cognitive learning outcomes towards a material as well as student skills in mastering technology.